Recontextualizing the Juridical Foundations of Islamic Banking Contracts through the Lens of Qawāʿid Maṣrafiyyah - Shofiyulloh; Rufaida, Arini (International Journal of Social Science and Religion (IJSSR), 2025)
This research analyzes the regulatory complexities inherent in Islamic banking contracts by adopting the framework of qawāʿid maṣrafiyyah (Islamic banking legal maxims), aiming to establish a more actionable and context-sensitive model of sharīʿah-compliant legitimacy. It critically addresses the lack of innovation in contract development, which is primarily attributed to the entrenched influence of rigid and literalist fiqh interpretations that narrowly frame legal reasoning within the dichotomy of ḥalāl and ḥarām. Through a content analysis approach combined with the methodological tools of uṣūl al-fiqh, this study endeavors to revitalize the operational relevance of legal maxims, particularly in addressing the complex realities of modern Islamic financial transactions. The ultimate goal is to broaden the interpretive framework available to Islamic legal scholars, enabling them to craft more responsive and forward-looking contractual models that align with the evolving dynamics of the global banking landscape. Key contributions of this study include: (1) the formulation of a normative and adaptable regulatory structure for Islamic banking contracts; (2) the reconfiguration of qawāʿid maṣrafiyyah as a practical and situationally attuned regulatory alternative; and (3) the inductive derivation of these maxims from the empirical challenges encountered in the Islamic banking industry.